Use of monitoring and evaluation for oversight and accountability by the Ekurhuleni Legislature - Malatjie, Matlala Maureen (My University, 2017)
Legislatures at all levels are tasked with the oversight of the executive. However, one of the challenges identified in oversight is the ineffectiveness of legislatures resulting from the executive not being held accountable for performance, and the need to strengthen oversight processes to ensure better monitoring of performance. These issues are also a challenge in the Ekurhuleni Legislature, where issues such as request for information yielding information that is not comprehensive from the executive; as well as a need to strengthen monitoring practices and assess service delivery impact. The aim of the research study is to assess the use of monitoring and evaluation practices by the Ekurhuleni Legislature for oversight and accountability as the cornerstone of legislatures across the spectrum. In answering this question, the study leaned to a qualitative research methodology that made use of a case study approach. The data was collected through respondent interviews, which was triangulated by use of document analysis as a secondary data collection method. The key findings of the research were grouped into four themes with each having its own sub-theme. One of the themes making up the findings of the study was that performance monitoring of the executive focused on analysis of documents and reports, which did not assess the realization of the outcomes and impacts of service delivery initiatives. The study found that no evaluation studies were conducted which would determine whether the realization of the municipality’s objectives was achieved. The structure of the oversight, monitoring and evaluation function was identify as an impediment in the function of oversight and accountability due to a lack of personnel who are equipped in monitoring and evaluation practices which would play a role in sound decision making. The additional findings of the study were that the lack of skilled personnel in M&E put the Legislature at a disadvantage when having to approve what to monitor in the results framework of the municipality. No meaningful inputs or recommendation has been made by the Legislature in this regard. The key recommendations that emanate from the study are that there is a need to strengthen performance monitoring by ensuring that the oversight goes beyond merely monitoring reports that have been sent to the Council. This will involve actively conducting more FISs and engaging with all operational and strategic plans of the municipality to ensure that all processes in the service delivery value chain are monitored, and that the responsible managers are held accountable for poor performance. The research also recommends that the Legislature inculcate evaluative studies to determine whether the service delivery impact of the municipality have been met and to what degree. The imposing of sanctions is also recommended as an accountability measure. The last recommendations put forth the need to capacitate the already existing personnel on M&E practices for the purpose of improving effective oversight and accountability.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the Field of Public and Development Sector Monitoring and Evaluation (MM M&E). April 2017
Keywords: Legislative power--South Africa; Legislative bodies--South Africa